A new coumarin based Schiff base fluorescence probe for zinc ion - Arvas, Busra; Ucar, Burcu; Acar, Tayfun; Arvas, Melih Besir; Sahin, Yucel; Aydogan, Feray; Yolacan, Cigdem (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Herein, a novel coumarin-based fluorescent probe (FS3) was designed, synthesized, and characterized. It exhibited significant fluorescence quenching in the presence of Zn2+ ions. Just a minor alteration occurred in the fluorescence intensity of FS3 in the presence of other metals studied. The limit of detection for the determination of Zn2+ by FS3 was calculated to be 3.43 x 10(-9) M. Since the Job's graph of 1/(F-0-F) and 1/[Zn2+] had a linear fit, it was determined that the binding stoichiometry between the FS3 and Zn2+ was 1:1. The association constant of the system was found to be 2.39 x 10(4) M-1 and confirmed by ESI-MS and FT-IR. It was demonstrated that the developed highly reversible sensor system works by performing real sample analysis. Moreover, the FS3 which has shown no toxicity and displayed a strong fluorescence image will act as an efficient and non-destructive sensor for the determination of Zn2+ in living organisms. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Coumarin; Fluorescent probe; Chemosensor; Zinc ion detection; Cell imaging; SELECTIVE DETECTION; COLORIMETRIC PROBE; ZN2+; DERIVATIVES; CADMIUM; PRECONCENTRATION; ENHANCEMENT; ELECTRODE; SENSORS; Chemistry